Membangun Ekonomi Desa dengan Pengembangan Desa Tematik sebagai Destinasi Pariwisata di desa Wanayasa, Purwakarta, Jawa Barat - Marsdenia, Marsdenia (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This Paper is a result of community engangement activies aimed to described how economic development of Wanayasa society through tematic village which as a tourism destination in the city of Purwakarta and food and non food product. This paper try to explore any possibility of Wanayasa to be a tematic village through to ways. Method of this paper is qualitative approached by using focus group discussions, indepth intervies and visiting site. There are two important result of this community engangement activities. there two possibility to create tematic vilage of wanayasa, as product, by using tea leaved and by using tourism approach as wnayasa habe Goa Jepang (japanese cave). There are some limitations to develop such a tematic village in Wanayasa, such as less of infrastructured arround goa jepang. Limitations of village tematic by using product approach is lack of skill and lack of distribution and marketing of the product either food or non food.